On-Line Impedance Measurement of Transmission Lines Using A Microprocessor and A Fast Multiplier - Kulkarni, Meera (My University, 1980)
A system is designed for calculating on-line digital impedance of a transmission line using a Microprocessor (Intel 8085) and a Fast Multiplier (TRW TDC 1003J). The approach taken is to use a digital filter to extract the fundamental component of voltage V and current I, then the impedance is given by V/I. The filter is of the sliding or running spectral measurement type. The total time taken for impedance calculation is 1.033 msec for 16 samples in a cycle at the power line frequency of 60 Hz. The maximum absolute error is ±1.52% the largest possible impedance value.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering